Reconstructing animated eye movements from electrooculography data to aid the diagnosis of vestibular disorders. (3rd January 2022) - Newman, Jacob L.; Phillips, John S.; Cox, Stephen J.
Abstract: Objective: To develop a method of visualising electrooculography data to improve the interpretability of nystagmus eye-movements captured using the Continuous Ambulatory Vestibular Assessment (CAVA ® ) device. Design: We are currently undertaking a clinical investigation to evaluate the capabilities of the CAVA ® device to detect periods of pathological nystagmus. The work presented here was undertaken using unblinded data obtained from the preliminary phase of this investigation. Study sample: One patient with Ménière's disease and one with Benign Paroxysmal Positional Vertigo. Results: Using the electrooculography data captured by the CAVA ® device, we reconstructed 2D animations of patients' eye movements during attacks of vertigo. We were able to reanimate nystagmus produced as a consequence of two conditions. Concurrent video footage showed that the animations were visually very similar to the patient's actual eye-movements, excepting torsional eye-movements. Conclusions: The reconstructed animations provide an alternative presentation modality, enabling clinicians to largely interpret electrooculography data as if they were present during a vertigo attack. We were able to recreate nystagmus from attacks experienced in the community rather than a clinical setting. This information provides an objective record of a patient's nystagmus and could be used to complement a full neurotologic history when considering diagnosis and treatment options.